Gluten-free living in China: The characteristics, food choices and difficulties in following a gluten-free diet – An online survey. (1st August 2018) - Lu, Zhenxing; Zhang, Haoyang; Luoto, Sanna; Ren, Xiang
Abstract: Background: Individuals adhering to a gluten-free diet (GFD) have been scarcely researched within a Chinese population. This present study was conducted to assess the characteristics, food choices, shopping preferences, and emotions and attitudes of individuals following a GFD. Methods: Individuals following a GFD were invited to complete an online questionnaire about their demography and geography characteristics, gluten-free food choices, shopping preferences, GFD management and subjective difficulty towards the diet. Distribution of the characteristics was described, and univariate and multivariate logistic regressions performed to explore the relationship between the above-mentioned variables and subjective difficulty in following a GFD. Result: 209 individuals following a GFD completed the questionnaire, most of whom were young, single and well-educated females from developed provinces or municipalities in China. Multiple regression showed that age, education level, advice on starting a GFD, duration before discovering a gluten intolerance, food choices and ways of GFD management were significantly associated with the subjective difficulty in following a GFD. Conclusion: Our findings offer a basic characteristics pattern of the population on a GFD in mainland China. Nearly one-third of GFD followers found the diet challenging to be followed. We suggest that sufficient celiac disease and gluten-induced disorder education be conducted among healthcare practitioners. Early diagnosis of gluten-induced disorders and defining an Asian-adapted GFD, as well as an increase in public awareness, may help adherence to a strict GFD in China.